Systematic Literature Review: The Role of Earth’s Magnetic Field in Dolphin Migration Navigation - Hadi Kesuma, Selfa Raya; Nainggolan, Gabrie Tamahra; Tanjung, Yul Ifda; Tariza Fairuz (Journal of Innovative Physics Teaching, 2025)
The urgency of this study arises from the need to understand how dolphins navigate long-distance migrations in marine environments where visual and acoustic cues are limited. The main problem addressed is the limited integration of scientific evidence on magnetoreception and the extent to which human-generated electromagnetic activities disrupt geomagnetic navigation. This study aims to synthesize recent findings on how dolphins detect and use the Earth’s magnetic field as a natural orientation system and to identify factors that threaten its stability. A Systematic Literature Review (SLR) using PRISMA guidelines was employed to ensure a structured process of identifying, screening, and synthesizing relevant peer-reviewed publications from 2014 to 2025. Five studies that met the inclusion criteria were analyzed thematically. The results show that magnetite-based receptors in the dolphin nervous system allow detection of geomagnetic variations and support the formation of internal spatial maps. Magnetoreception is strengthened through its integration with echolocation and passive electroreception, forming a multisensory navigation system. The findings also indicate that artificial electromagnetic sources, such as submarine cables and sonar, can interfere with geomagnetic cues and reduce navigational accuracy. These results provide implications for conservation and biomimetic technology development.